Normal and anomalous development of visual motion processing: motion coherence and 'dorsal-stream vulnerability'. - Braddick, O; Atkinson, J; Wattam-Bell, J (2003)
Directional motion processing is a pervasive and functionally important feature of the visual system. Behavioural and VEP studies indicate that it appears as a cortical function after about 7 weeks of age, with global processing, motion based segmentation, and the use of motion in complex perceptual tasks emerging shortly afterwards. A distinct, subcortical motion system controls optokinetic nystagmus (OKN) from birth, showing characteristic monocular asymmetries which disappear as binocular cortical function takes over in normal development. Asymmetries in cortical responses are linked to this interaction in a way that is not yet fully understood. Beyond infancy, a range of developmental disorders show a deficit of global motion compared to global form processing which we argue reflects a general 'dorsal-stream vulnerability'.